Reconstruction of Islamic Education (Study of Islamic Education Thoughts of Prof. Dr. Muhaimin, M.A.) - Pita Anjarsari; Happy Susanto (At-Ta'dib, 2019)
The aims of this paper is to examine the thoughts of Prof. Dr. Muhaimin. MA about the reconstruction of Islamic education. The development of Islamic education in schools is a culture of quality and quantity and will be used as a platform, values, enthusiasm, attitudes, and behaviors for education as a lactor in the school environment. Muhaimin offers a reconstruction of Islamic education by offering a modernization paradigm in education because it was considered more ideal to be applied in the arena of the development of Islamic education. Meanwhile, the educational theory used was in accordance with the education theories of the Neo-modernists namely by continuing to actualize old theories that were still compatible with the demands times accompanied by new innovations in education. In that context, renewal of Islamic education according to Muhaimin must be done by conducting integrated and multicultural-based education. The idea of renewing Islamic education offered includes implementing Islamic Religious Education learning that is integrated with a multicultural-based approach to inquiry and Islamic education, namely developing education through the learning of contextual and research-based Islamic religion. Actualization of the thought above is based on the modernization paradigm and Neo-modernist theory both at university and at school.